PENGARUH UPAH MINIMUM, PENDIDIKAN DAN JUMLAH PENDUDUK TERHADAP PENGANGGURAN TERBUKA DI JAWA TENGAH - Diary Yulia Nur Adinda; Wenny Restikasari (Jurnal Ekonomika : INDEPENDEN, 2026)
The open unemployment rate in Central Java Province remains a significant issue, despite positive increases in minimum wages, education, and population during the 2020–2024 period. Increases in the minimum wage and average years of schooling have not fully addressed the disparity in job opportunities between regions, resulting in uneven labor distribution across districts or cities.This study analyzes the effect of minimum wages, education, and population on the open unemployment rate in Central Java Province during the period 2020-2024. This study uses panel data with the Fixed Effect Model (FEM) approach and utilizes secondary data from 35 regencies/cities in Central Java. The model estimation results show that the minimum wage, education, and population variables simultaneously have a significant effect on the open unemployment rate in Central Java. Partially, the minimum wage and education variables have a negative and significant effect on the unemployment rate. Meanwhile, the population variable has a positive and insignificant effect on the unemployment rate. The government is expected to pay serious attention to the minimum wage system, improving the quality of education, and the availability of job opportunities.